Study Of The Meaning Of The Prohibition Of Sleeping After Fajr With A Scientific Approach In The Hadith Narrated By Abu Daud Index Number 2606 - Wulandari, Widiana Putri; Nurita, Andris (Taqaddumi: Journal of Quran and Hadith Studies, 2024)
Sleep is a necessity for every human being in everyday life. However, several times are not recommended, including sleeping after dawn. In the hadith, it is also mentioned that the Prophet forbade his people to sleep after dawn. However, not all hadiths are authentic and can be used as evidence. Therefore, it is necessary to re-examine the validity and meaning of the hadith. To examine the meaning of the hadith, the author uses the study of tahlili. This study aims to describe the prohibition of sleeping after dawn from the hadith perspective with a scientific approach. The method used in this research is the descriptive qualitative method. The results of this study prove that sleeping after dawn is not suitable for health, and the views of the scholars regarding sleeping after dawn are highly discouraging and make it a habit.